Structures of Discoidal High Density Lipoproteins: A COMBINED COMPUTATIONAL-EXPERIMENTAL APPROACH - Gu, Feifei (American Society for Biochemistry and Molecular Biology, 2010)
Conversion of discoidal phospholipid (PL)-rich high density lipoprotein (HDL) to spheroidal cholesteryl ester-rich HDL is a central step in reverse cholesterol transport. A detailed understanding of this process and the atheroprotective role of apolipoprotein A-I (apoA-I) requires knowledge of the structure and dynamics of these various particles. This study, combining computation with experimentation, illuminates structural features of apoA-I allowing it to incorporate varying amounts of PL. Molecular dynamics simulated annealing of PL-rich HDL models containing unesterified cholesterol results in double belt structures with the same general saddle-shaped conformation of both our previous molecular dynamics simulations at 310 K and the x-ray structure of lipid-free apoA-I. Conversion from a discoidal to a saddle-shaped particle involves loss of helicity and formation of loops in opposing antiparallel parts of the double belt. During surface expansion caused by the temperature-jump step, the curved palmitoyloleoylphosphatidylcholine bilayer surfaces approach planarity. Relaxation back into saddle-shaped structures after cool down and equilibration further supports the saddle-shaped particle model. Our kinetic analyses of reconstituted particles demonstrate that PL-rich particles exist in discrete sizes corresponding to local energetic minima. Agreement of experimental and computational determinations of particle size/shape and apoA-I helicity provide additional support for the saddle-shaped particle model. Truncation experiments combined with simulations suggest that the N-terminal proline-rich domain of apoA-I influences the stability of PL-rich HDL particles. We propose that apoA-I incorporates increasing PL in the form of minimal surface bilayers through the incremental unwinding of an initially twisted saddle-shaped apoA-I double belt structure.